Variations of Speech Act Realizations in The Jakarta Post Readers’ Forum - Sinta Sestiana (Universitas Pendidikan Indonesia (UPI), 2013)
The research investigated variations of speech act realizations in The Jakarta Post readers’ forum. The research focused on the speech acts found in The Jakarta Post readers’ forum and the variations made when a speech act was realized by using a speech acts theory proposed by Bach and Harnish (1979). Based on the theory, speech acts are classified into four major categories in which each category consists of subcategories in a system namely, a taxonomy of communicative illocutionary acts. The data were obtained from six pages of The Jakarta Post readers’ forum online edition under the heading of the topic about a lack of religious tolerance. The data were analyzed by categorizing the kinds of speech acts and the variations of each category according to speech acts classification provided by the taxonomy. The research founds that the kinds of speech acts realized by the contributors to the readers’ forum were Constatives, Acknowledgments and Directives. Each of which was comprised of finer classes of speech act variations. The research concluded that the readers’ forum has been used to serve several functions in accommodating its contributors’ beliefs, feelings and desires. The contributors provided many reasons in form of beliefs to encourage a reasonableness of the blaming/complaint/critique or even an urgency of the order/asking/advice.Keywords: Speech acts, Speech acts schema, Taxonomy of communicative illocutionary acts